PENGARUH TEACHING FACTORY DAN MOTIVASI MEMSASUKI DUNIA KERJA TERHADAP KESIAPAN KERJA SISWA SMK YANG DIMODERASI SELFEFFICACY - Meirida Kartika Jati; Dewi Kusuma Wardani (STKIP Persada Khatulistiwa Sintang, 2025)
The purpose of this study is to examine the extent to which the implementation of teaching factory and the motivation to enter the workforce influence students’ work readiness, with self-efficacy acting as a moderating variable. The population of this research consisted of 703 students from grade XI and XII at SMKN 1 Surakarta, with a sample of 255 respondents. This study employed a descriptive quantitative method with an ex post facto approach. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA) with SPSS 23. The results indicate that the implementation of teaching factory and the motivation to enter the workforce have a positive and significant effect on students’ work readiness. Self-efficacy does not moderate the relationship between teaching factory and work readiness, but significantly and negatively moderates the effect of work motivation on work readiness. Therefore, students’ work readiness can be improved through the strengthening of teaching factory and motivation, while taking into account the role of self-efficacy.